2015
DOI: 10.1099/ijsem.0.000423
|View full text |Cite
|
Sign up to set email alerts
|

Planococcus faecalis sp. nov., a carotenoid-producing species isolated from stools of Antarctic penguins

Abstract: Taxonomic studies were performed on a novel carotenoid-producing strain, designated AJ003 Based on the phenotypic, chemotaxonomic and phylogenetic data, strain AJ003

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Five isolates were affiliated to the phylum Bacteroidetes, and belong to the genera Zobellia , Chryseobacterium and Flavobacterium , and the other four isolates were affiliated to the phylum Firmicutes and assigned to Planococcus genus. All genera mention above have been previously reported in Antarctica, and they were characterized as pigmented [ [29] , [30] , [31] ]. In particular, strain P33 was assigned to Flavobacterium genus with a 96% similarity, indicating that it could be a new specie.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five isolates were affiliated to the phylum Bacteroidetes, and belong to the genera Zobellia , Chryseobacterium and Flavobacterium , and the other four isolates were affiliated to the phylum Firmicutes and assigned to Planococcus genus. All genera mention above have been previously reported in Antarctica, and they were characterized as pigmented [ [29] , [30] , [31] ]. In particular, strain P33 was assigned to Flavobacterium genus with a 96% similarity, indicating that it could be a new specie.…”
Section: Resultsmentioning
confidence: 99%
“…Even though strains belonging to Planococcus genus have been widely reported as pigmented strains, the identification of carotenoids produced by Planococcus is scarce in the literature. Shindo et al [ 5 ] reported that P. maritimus produced methyl glucosyl-3,4-dehydro-apo-8′-lycopenoate, and Kim et al [ 29 ] that P. faecalis produced glycosyl-4,4′-diaponeurosporen-4′-ol-4 oic acid as major pigment, and both are C30 carotenoids. However, C.p.…”
Section: Resultsmentioning
confidence: 99%
“…The main type of carotenoid produced by Planococcus species has been described as Glyco-C30-carotenoic acid. These terpenoids possess a chain of 30, 40 or 50 carbons, with absorption peaks at 450-490 nm (Kim et al, 2015;Ganapathy et al, 2016). The Planococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Planococcus was originally described by Migula (1895). There were 16 valid species in the genus Planococcus until recently: P. citreus (Migula, 1895), P. kocurii (Hao & Komagata, 1985), P. antarcticus (Reddy et al, 2002), P. maritimus (Yoon, Weiss, Kang, Oh, & Park, 2003), P. maitriensis (Alam, Singh, Dube, Reddy, & Shivaji, 2003), P. rifietoensis (Romano, Giordano, Lama, Nicolaus, & Gambacorta, 2003), P. columbae (Suresh, Mayilraj, Bhattacharya, & Chakrabarti, 2007), P. donghaensis (Choi et al, 2007), P. salinarum (Yoon, Kang, Lee, Oh, & Oh, 2010), P. halocryophilus (Mykytczuk, Wilhelm, & Whyte, 2012), P. plakortidis (Kaur et al, 2012), P. soli (Luo et al, 2014), P. faecalis (Kim, Kang, Yu, Kim, & Lee, 2015), P. ruber (Wang et al, 2017), P. salinus (Gan, Zhang, Tian, et al, 2018), and P. halotolerans (Gan, Zhang, Zhang, et al, 2018). Due to their phenotypic properties, menaquinone profiles, fatty acid composition and G + C content in the DNA, the species Planococcus mcmeekinii (Yoon et al, 2001), Planococcus okeanokoites (Yoon et al, 2001), Planococcus alkanoclasticum (Dai, Wang, Wang, Liu, & Zhou, 2005), Planococcus psychrophilum (Dai et al, 2005), and P. stackebrandtii (Jung, Kang, Oh, Yoon, & Kim, 2009) were reclassified to genus Planomicrobium , and Planococcus halophilus was cataloged to the genus Marinococcus (Hao, Kocur, & Komagata, 1984; Novitsky & Kushner, 1976).…”
Section: Introductionmentioning
confidence: 99%